Attachment style, ways of coping with stress and life attitudes by MSM who are active chemsex users - P. Kaluzny; R. Kowalczyk (European Psychiatry, 2022)
Introduction The research was carried out in Poland between 7-19 March 2021 with the help of online questionnaire on a group of 183 male aged 18-20. The subjects were divided into two age groups: 18-29 and 30-40. The second division are chemsex and non chemsex users.